Ecology of wild ducks in inland Australia - Frith, H J (Wildfowl, 1961)
In inland Australia waterfowl habitats fluctuate greatly in extent from year to year. Small areas of permanent habitats occur but the most extensive habitats are those that are formed periodically and erratically by flooding of the rivers. The movement patterns of the various species of wild ducks that inhabit the region vary according to the habitat occupied by the species and vary in regularity according to the permanence of the habitat. Species which are confined to the permanent swamps are very regular in movement, being either sedentary or regularly migratory, but those that utilize the more temporary habitats have developed nomadic habits to a very high degree. The degree of mobility of the different species is related to their food requirements. The species having regular movements have regular food cycles. Some nomadic species have very adaptable food habits and can utilize a very wide variety of foods, thus being able to exploit all types of water as they occur. One nomadic species, however, is a food specialist and accordingly has developed an extreme type of nomadic wandering. The species characteristic of permanent swamps have very regular breeding seasons but the nomadic species are able to breed at any time of the year whenever suitable conditions occur. The sexual cycle culminating in breeding is initiated by increasing water level in rivers. In this manner whenever flooding occurs the birds breed in the newly developed floodwater. The same factor, increasing water level, that initiates breeding in the birds initiates breeding in the animals forming the food of the ducklings so that abundant food is available.